Distribusi Hasil Tangkapan Ikan Pelagis pada Perikanan Purse Seine Berdasarkan Parameter Lingkungan Perairan di Kabupaten Pati - Ganang Dwi Prasetyo; Mohammad Akhid Yunanto; Rafis Tri Sandi Dimu; Sugiono Sugiono (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
Purse seine is an effective device to catching pelagic fish. One of the reasons for the decline in pelagic catches is due to changes in environmental conditions every year, making it difficult to predict. This study aims to determine the distribution of pelagic fish catches associated with oceanographic parameters such as Sea Surface Temperature (SST) and chlorophyll-a. The research was conducted in November 2019 – March 2020 with direct observation where the total fishing operations were 98 times the setting. The sampling technique used was purposive sampling method, while the oceanographic parameters of SST and chlorophyll-a were obtained from the Modis-Aqua Level 3 on the NASA ocean color web. The results showed that the total weight of the catch was 183.410 kg, dominated by Decapterus sp. of 46,98% and the minimum caught was Sphyraena sp. and Istiophorus sp. with percentage of 0,05%. The highest catche occurred in November 2019 with an average temperature of 29,25°C and a chlorophyll-a concentration of 0,268 mg/m3, where suspected that the correlation between Decapterus sp. distribution with SST and the concentration of chlorophyll-a was negative.